Digital cities the Internet and the geography of opportunity - Mossberger, Karen; Tolbert, Caroline J.; Franko, William (New York : Oxford University Press, 2013)
Federal broadband policy has largely ignored urban areas, where most Americans live. Using an original and unprecedented multi-level analysis of access and use in low-income neighbourhoods, 'Digital Cities' tells the story of information technology use and inequality in American cities and metropolitan areas.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Internet -- Government policy -- Illinois -- Chicago; Computer networks -- Social aspects -- Illinois -- Chicago; Digital divide -- Illinois -- Chicago; Internet -- Government policy -- United States; Computer networks -- Social aspects -- United States; Digital divide -- United States